math

posted by .

use substitution to solve system
-2x+y= -9
=5x+4y= -30

  • math -

    hmmm. you must really be confused; not only at a loss, but at a lost!

    we see that
    -2x+y = -9, so
    y = 2x-9

    now substitute that into the other equation:

    5x+4(2x-9) = -30
    13x = 6
    x = 6/13
    so, y=2x-9 = -105/13

    The =5x+4y confuses me. If that was supposed to be -5x, then

    -5x+4(2x-9) = -30
    3x = 6
    x=2

    which seems like a better answer.

Respond to this Question

First Name
School Subject
Your Answer

Similar Questions

  1. Substitution Method-Plz help

    Use the Substitution method to solve the system of equations. x + y = -4 x - y = 2 solve for x in the second equation. x= y+2 Put that in for x in the first equation: x+y=-4 (y+2) + y = -4 solve for y. Then, x= y+2 i don't get it.How …
  2. math

    solve each system of equations by substitution. y=3x-9 please help explain how to solve this using substitution.
  3. maths

    use the substitution method to solve the linear system. 1. 3x=9 -x+2y=9 3x/3 = 9/3 x = 3 -x(3)+2y = 9 -3+2y = 9 2y = 12 y = 6 is (3,6) correct?
  4. algebra

    i need help with these problems (either a solution or how to plug them into a graphing calculator): 1) Solve by substitution or elimination 4/x + 1/y + 2/z = 4 2/x + 3/y - 1/z = 1 1/x + 1/y + 1/z = 4 2)Solve the system of equations …
  5. Algebra 1- Math

    use substitution to solve the system 2x-y=-4 -3x+y=-9
  6. math

    use the substitution to solve the system -5x+24=27 y=2x+11 x= y=
  7. math

    use substitution to solve the system -5x+2y=27 y=2x+11 x= y=
  8. Math Homework

    Hello! I need help with these math questions, thanks! :) 1.) Solve the system by substitution. 5x + 2y = -17 x = 3y 2.) Solve the system by substitution. x/3 + y = 4/3 -x + 2y = 11 3.) Solve the system by elimination. 2x - 3y = 0 2x …
  9. Math

    Use substitution to solve the system. 3x+5y=21 y=2x-1
  10. Math

    17) solve this linear system using the method of substitution. 2y-x=-10 y= -3/2x-1 20) simplify then solve by substitution 2(x-4)+y=6 3x-2(y-3)=13 just need help with these 2.

More Similar Questions